2014
DOI: 10.1371/journal.pone.0114244
|View full text |Cite
|
Sign up to set email alerts
|

Polarity Specific Effects of Transcranial Direct Current Stimulation on Interhemispheric Inhibition

Abstract: Transcranial direct current stimulation (tDCS) has been used as a useful interventional brain stimulation technique to improve unilateral upper-limb motor function in healthy humans, as well as in stroke patients. Although tDCS applications are supposed to modify the interhemispheric balance between the motor cortices, the tDCS after-effects on interhemispheric interactions are still poorly understood. To address this issue, we investigated the tDCS after-effects on interhemispheric inhibition (IHI) between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 61 publications
5
39
1
Order By: Relevance
“…Cathodal ipsilateral stimulation might have improved performance by a reduction of interhemispheric inhibition. This effect of interhemispheric interaction on cortical excitability induced by motor cortex tDCS has also been described in adults (Tazoe et al, 2014). Taking into account the excitabilityenhancing effect of 1 mA cathodal tDCS in children in the study of Moliadze et al (2015a), it cannot be ruled out, however, that excitability-enhancing ipsilateral tDCS had a performance-improving effect.…”
Section: Healthy Childrenmentioning
confidence: 68%
“…Cathodal ipsilateral stimulation might have improved performance by a reduction of interhemispheric inhibition. This effect of interhemispheric interaction on cortical excitability induced by motor cortex tDCS has also been described in adults (Tazoe et al, 2014). Taking into account the excitabilityenhancing effect of 1 mA cathodal tDCS in children in the study of Moliadze et al (2015a), it cannot be ruled out, however, that excitability-enhancing ipsilateral tDCS had a performance-improving effect.…”
Section: Healthy Childrenmentioning
confidence: 68%
“…Additionally, a small number of studies have found that anodal tDCS decreases local GABA concentration and increases local Glutamine concentration, whereas cathodal tDCS decreases local Glutamine concentration (Hunter et al, ; Kim, Stephenson, Morris, & Jackson, ; Stagg et al, ). These changes could underlie the observed, and differential, effects of tDCS on local excitatory and inhibitory circuits (Sasaki, Miyaguchi, Kotan, Kojima, & Kirimoto, ; Stagg & Nitsche, ; Tazoe, Endoh, Kitamura, & Ogata, ; Wiethoff, Hamada, & Rothwell, ). As local changes in the excitatory/inhibitory balance are thought to produce changes in large‐scale brain networks (Deco, Hagmann, Romani, Mantini, & Corbetta, ), this might provide a mechanism for the remote effects on network activity we observed.…”
Section: Discussionmentioning
confidence: 99%
“…This issue however, needs to be confirmed, given that only some studies have used high‐frequency rTMS because of the increased risk of seizure [32]. In addition, the comparison between anodal‐ and cathodal‐tDCS, both acting on IHI, yielded similar results [74]. The difference with rTMS findings may depend on the fact that tDCS has gross effects on brain excitability, and therefore it can less selectively shape IHI or finely modulate intracortical inhibitory and facilitatory networks (which in turn influence IHI) [75].…”
Section: Discussionmentioning
confidence: 98%